Handbook of research on multidisciplinary approaches to entrepreneurship, innovation, and ICTs - Carvalho, Luísa Cagica 1970-; Reis, Leonilde 1962-; Prata, Alcina 1969-; Pereira, Raquel (IGI Global, Publisher of Timely Knowledge, 2021)
"This book discusses the digitalization techniques of the modern workforce as well as important tools empowering social entrepreneurship initiatives" - Provided by publisher
Includes bibliographical references and index
Keywords: Entrepreneurship; Informationswirtschaft; Technische Innovation; Social entrepreneurship; Personnel management / Technological innovations; Information technology / Management; Aufsatzsammlung